Conventional Microsurgical Vasovasostomy Vs Z-plasty Vasovasostomy - Kazez, Ahmet; Özercan, İbrahim H.; Parmaksız, M. Ergun (Fırat University, 2002)
Objective: Microsurgically end-to-end anastomosis with interrupted sutures is gold standard for vasovasostomy. Stenosis or infertility may develop after this procedure. It has been reported that Z-plasty provides a better anastomotic patency rate in microvasculer anastomosis. An experimental study was designed to compare conventional microsurgery with Z-plasty anastomosis on vasovasostomy. Material and Methods: A total of 21 male Wistar-albino rats were divided into three groups (control, conventional microsurgical vasovasostomy, Z-plasty microsurgical vasovasostomy) each containing 7 rats. Anastomoses were carried out under an operating microscope with interrupted, single layer 10/0 Ethilon® sutures. After six weeks, their fertility rates, anastomotic patency rate and pathological changes in the area of anastomosis were assessed. The results were compared statistically. Results: The control group had a fertility rate of 70%, and fertility rates were 56% and 50% in the groups II and III, respectively. Anastomoses were obliterated in one (15%) in each test groups. Fertility rates and patency rate were not statistically significant in test groups. Inflammation seen around the anastomosis area in the Z-plasty group was more prominent than standard vasovasostomy applied-rats. Conclusions: It has been determined that application of Z-plasty to the standard anastomosis for vasovasostomy brings about an additional technical difficulty but does not provide any advantage as in vascular structures. The reasons for the failure of Z-plasty technique could be anatomical differences between ductus defference and vasculer sutructures. As a result, standard microsurgical vasovasostomy still seems to be the most valid method for vasovasostomy.

Amaç: Vazovazostomi için mikrocerrahi ile uç uca, tek tek anastomoz altın standarttır. Stenoz ve infertilite bu prosedürün komplikasyonlarıdır. Vasküler uygulamalarda Z-plastili anastomoz, açıklık için avantaj sağlamaktadır. Bu nedenlerle duktus deferes anastomozunda konvansiyonel mikrocerrahi ile Z-plastili mikrocerrahi anastomozun karşılaştırılması amaçlandı. Gereç ve Yöntem: Her birinde 7 Wistar-albino tipi rat bulunan üç grupta (Kontrol, Standart mikrocerrahi anostomoz, Z- plasti uygulanan mikrocerrahi anostomoz) gerçekleştirildi. Anastomozlar ameliyat mikroskobunda mikrocerrahi ilkeleri ile, 10/0 Ethilon® ile uygulandı. İşlem sonrası fertilite oranları, sperm granulomları, anastomoz açıklığı ve anastomoz alanlarındaki histopatolojik değişiklikler karşılaştırıldı. Bulgular: Kontrol grubunda fertilite oranı %70, Grup 2'de %6 ve Grup 3'de %50 olarak bulundu. Her iki deney grubunda birer anastomoz oblitere olmuştu (%15). Grup 2 ve 3'ün fertilite oranları kendi aralarında anlamsız iken kontrol grubu ile aralarındaki fark anlamlı idi. Anastomoz çaplarında da istatistiksel farklılık görülmedi. Z-plasti grubunda anastomoz alanındaki enflamasyon standart anastomoz grubuna göre daha fazla olarak belirlendi. Sonuçlar: Z-plasti uygulaması standart anastomoza göre teknik güçlükler eklemekle birlikte standart vazo-vazostomiye ek bir avantaj sağlamamıştır. Bunun muhtemel nedeni vasküler yapılarla duktus deferens arasındaki anatomik farklılıklar olabilir. Vazo-vazostomi için standart mikrocerrahi hala en geçerli yöntem olarak görünmektedir.
Z-plasti Vazovazostominin Standart Mikrocerrahi Anastomozla Karşılaştırılması